Simple-Zero and Double-Zero Singularities of a Kaldor-Kalecki Model of Business Cycles with Delay - Xiaoqin P. Wu (Discrete Dynamics in Nature and Society)
We study the Kaldor-Kalecki model of business cycles with delay in both the gross product and the capital stock. Simple-zero and double-zero singularities are investigated when bifurcation parameters change near certain critical values. By performing center manifold reduction, the normal forms on the center manifold are derived to obtain the bifurcation diagrams of the model such as Hopf, homoclinic and double limit cycle bifurcations. Some examples are given to confirm the theoretical results.